Expression of the Testis-Specific Serine/Threonine Kinases Suggests Their Role in Spermiogenesis of Bay Scallop Argopecten irradians - Xue, Xinru; Zhang, Lingling; Li, Yajuan; Wei, Huilan; Wu, Shaoxuan; Liu, Tian; Liu, Liangjie; Xing, Qiang; Wang, Shi; Bao, Zhenmin (Frontiers in Physiology, 2021)
Members of the testis-specific serine/threonine kinases (Tssk) family play critical roles in spermatogenesis in vertebrates. But in mollusks, research on Tssk family is still lagging. In this study, we systematically identified Tssk family based on the genomic and transcriptomic data from a commercially important scallop Argopecten irradians and detected the spatiotemporal expression in adult gonads. Five members were identified, with the gene length varying from 1,068 to 10,729 bp and the protein length ranging from 294 to 731 aa. All the Tssks possess a serine/threonine protein kinase catalytic (S_TKc) domain. Phylogenetic analysis revealed existence of four homologs of vertebrate Tssk1/2, Tssk3, Tssk4, Tssk5, and absence of Tssk6 in the scallop. The remaining gene (Tssk7) formed an independent clade with Tssks of other mollusks and arthropods, indicating that it may be a new member of Tssk family unique to protostomes. By investigating the expression of Tssks in four developmental stages of testes and ovaries, we found all five Tssks were primarily expressed in mature testis. In situ hybridization experiment revealed the five Tssks were localized in the spermatids and spermatozoa. The testis-predominant expression of Tssk family suggests Tssks may play pivotal roles in spermiogenesis in the scallop. Our study provides basic information on the characteristics and expression profiles of Tssk family of A. irradians. To our knowledge, it represents the first comprehensive analysis of Tssk family in mollusks.